2004
DOI: 10.1007/s00134-003-2152-x
|View full text |Cite
|
Sign up to set email alerts
|

Application of therapeutic hypothermia in the ICU: opportunities and pitfalls of a promising treatment modality. Part 1: Indications and evidence

Abstract: Although induced hypothermia appears to be a highly promising treatment, it should be emphasized that it is associated with a number of potentially serious side effects, which may negate some or all of its potential benefits. Prevention and/or early treatment of these complications are the key to successful use of hypothermia in clinical practice. These side effects, as well as various physiological changes induced by cooling, are discussed in a separate review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
369
0
40

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 414 publications
(414 citation statements)
references
References 199 publications
5
369
0
40
Order By: Relevance
“…On the other hand, also in the experimental ischemic BVA, cerebral cooling decreased the volume of the infracted region 16 . After CA, increase of the systemic temperature can be noted and consequent cerebral hyperthermia.…”
Section: Temperaturementioning
confidence: 89%
See 2 more Smart Citations
“…On the other hand, also in the experimental ischemic BVA, cerebral cooling decreased the volume of the infracted region 16 . After CA, increase of the systemic temperature can be noted and consequent cerebral hyperthermia.…”
Section: Temperaturementioning
confidence: 89%
“…In the injured brain this difference is signifi cantly higher and may reach up to 3º C. In acute cerebral ischemia there is also a regional increase of temperature, asymmetric to the rest of the brain mass 16 . Animal studies have shown that increment of cerebral temperature is accompanied by neurological deterioration and that its controlled decrease reduces these injuries.…”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Hippocrates advocated the packing of wounded soldiers in snow and ice in 400 BC [10]. Clinical interest in hypothermia was regained in the 1930s and 1940s, with observations and case reports describing successful resuscitation of drowning victims who were hypothermic, even after prolonged periods of asphyxia [11]. The first scientific report describing clinical applications of TH in traumatic brain injury (TBI) was published in 1943 [12].…”
Section: Historical Aspectsmentioning
confidence: 99%
“…During the maintenance phase, tight control of the target temperature should be achieved, with minor or no fluctuations (maximum, 0.2°C to 0.5°C). In this phase, attention should shift toward the prevention of longer term side effects, such as pneumonia, wound infections, and bedsores [60]. Finally, the rewarming phase can lead to severe electrolyte abnormalities (mostly hyperkalemia), caused by shifts from the intracellular to the extracellular compartment, and elevation of ICP.…”
Section: Initiation Of Therapeutic Hypothermiamentioning
confidence: 99%